Tolerogenic Vaccination with MOG/VitD Overcomes Aggravating Effect of C. albicans in Experimental Encephalomyelitis - Fraga-Silva, Thais F.C. [UNESP]; Mimura, Luiza A.N. [UNESP]; Zorzella-Pezavento, Sofia F.G. [UNESP]; Ishikawa, Larissa L.W. [UNESP]; França, Thais G.D. [UNESP]; Thomé, Rodolfo; Verinaud, Liana; Arruda, Maria S.P. [UNESP]; Sartori, Alexandrina [UNESP] (Wiley, 2016)
Aims: Multiple sclerosis (MS) is an immune-mediated demyelinating disorder of the central nervous system (CNS). We described that Candida albicans (Ca) aggravates experimental autoimmune encephalomyelitis (EAE) that is a model to study MS. We also observed that vaccination with a myelin peptide (MOG) in the presence of vitamin D (VitD) protected mice against EAE. In this work, we investigated whether Ca infection interferes with the efficacy of this vaccine. Methods: EAE was induced in C57BL/6 female mice previously vaccinated with MOG+VitD and then infected 3 days before encephalomyelitis induction. Results: Vaccination was able to control EAE development in infected mice. These animals gained weight, and only a few progressed to very low clinical scores. Protection was confirmed by a lower inflammatory infiltration in the CNS and was also associated with a reduced production of encephalitogenic cytokines by spleen and CNS cell cultures. The elevated percentage of CD25+FoxP3+ cells suggests that regulatory T cells are involved in the protection. Adoptive transfer of splenocytes from mice vaccinated with MOG+VitD supports the view that protection is mediated by immunoregulatory cells. Conclusion: Together, these experiments provide evidence demonstrating that EAE can be prevented by the inverse vaccination with MOG+VitD even in the presence of a disease-aggravating infectious agent.
Keywords: Active vitamin D; Disseminated candidiasis; Multiple sclerosis; Myelin oligodendrocyte glycoprotein; Tolerogenic vaccination